Proteomic Analysis of Zika Virus Infected Primary Human Fetal Neural Progenitors Suggests a Role for Doublecortin in the Pathological Consequences of Infection in the Cortex - Jiang, Xuan; Dong, Xiao; Li, Shi-Hua; Zhou, Yue-Peng; Rayner, Simon; Xia, Hui-Min; Gao, George F.; Yuan, Hui; Tang, Ya-Ping; Luo, Min-Hua (Frontiers in Microbiology, 2018)
Zika virus (ZIKV) infection is associated with severe neurological defects in fetuses and newborns, such as microcephaly. However, the underlying mechanisms remain to be elucidated. In this study, proteomic analysis on ZIKV-infected primary human fetal neural progenitor cells (NPCs) revealed that virus infection altered levels of cellular proteins involved in NPC proliferation, differentiation and migration. The transcriptional levels of some of the altered targets were also confirmed by qRT-PCR. Among the altered proteins, doublecortin (DCX) plays an important role in NPC differentiation and migration. Results showed that ZIKV infection downregulated DCX, at both mRNA and protein levels, as early as 1 day post infection (1 dpi), and lasted throughout the virus replication cycle (4 days). The downregulation of DCX was also observed in a ZIKV-infected fetal mouse brain model, which displayed decreased body weight, brain size and weight, as well as defective cortex structure. By screening the ten viral proteins of ZIKV, we found that both the expression of NS4A and NS5 were correlated with the downregulation of both mRNA and protein levels of DCX in NPCs. These data suggest that DCX is modulated following infection of the brain by ZIKV. How these observed changes of DCX expression translate in the pathological consequences of ZIKV infection and if other cellular proteins are equally involved remains to be investigated.